Variants of the IL‐10 gene associate with muscle strength in elderly from rural Africa: a candidate gene study. Issue 5 (18th July 2014) - Beenakker, Karel G. M.; Koopman, Jacob J. E.; van Bodegom, David; Kuningas, Maris; Slagboom, Pieternella E.; Meij, Johannes J.; Maier, Andrea B.; Westendorp, Rudi G. J.
Summary Recently, it has been shown that the capacity of the innate immune system to produce cytokines relates to skeletal muscle mass and strength in older persons. The interleukin‐10 (IL‐10) gene regulates the production capacities of IL‐10 and tumour necrosis factor‐α (TNF‐α). In rural Ghana, IL‐10 gene variants associated with different production capacities of IL‐10 and TNF‐α are enriched compared with Caucasian populations. In this setting, we explored the association between these gene variants and muscle strength. Among 554 Ghanaians aged 50 years and older, we determined 20 single nucleotide polymorphisms in the IL‐10 gene, production capacities of IL‐10 and TNF‐α in whole blood upon stimulation with lipopolysaccharide (LPS) and handgrip strength as a proxy for skeletal muscle strength. We distinguished pro‐inflammatory haplotypes associated with low IL‐10 production capacity and anti‐inflammatory haplotypes with high IL‐10 production capacity. We found that distinct haplotypes of the IL‐10 gene associated with handgrip strength. A pro‐inflammatory haplotype with a population frequency of 43.2% was associated with higher handgrip strength (P = 0.015). An anti‐inflammatory haplotype with a population frequency of 7.9% was associated with lower handgrip strength (P = 0.006). In conclusion, variants of the IL‐10 gene contributing to a pro‐inflammatory cytokine response associate with higher muscle strength, whereas those with anti‐inflammatory response associate with lower muscle strength. Future research needs to elucidate whether these effects of variation in the IL‐10 gene are exerted directly through its role in the repair of muscle tissue or indirectly through its role in the defence against infectious diseases.